O currículo de Química do Estado de São Paulo: Concepções de professores do Ensino Médio - SOUZA, Adriano Luiz de (2018)
Under the research program of Public Policies in Education, Educational Practices and Diversities of the Master’s degree in Education at the Universidade do Oeste Paulista, the present research is aimed to shed a light on the Chemistry school program of the public state education of São Paulo from the conception of teachers on its effectiveness. As a methodology, a field research was carried out with 26 professors teaching Chemistry in the state public school of São Paulo by applying a structured questionnaire with open and closed questions, focused on the objectives of this research. The research is descriptive-qualitative, and a descriptive analysis was performed in order to comprehend the results. In a more reviewing perspective, by conducting the present study, it was possible to verify the curriculum as a limitation to teach Chemistry, especially due to restrictions such as lack of contextualization to the student reality, contents presenting outdated information, lack of illustrations, inappropriate arrangement of Chemistry contents, superficiality and incomplete contents and activities. Among the limitations observed, there was the overuse of standards and of detailing the contents, suggesting that this aspect should be modified in the official curriculum by taking a more guiding role.